Turkey’s National Strategy on Regional Development (2014-2023) and a critical view of development corridors - Özbek, Oğuz (Narodowa Strategia Rozwoju Regionalnego Turcji na lata 2014-2023 a krytyczne spojrzenie na korytarze rozwoju, 2019)
This paper draws attention to various critical issues on new development corridors introduced in Turkey’s National Strategy on Regional Development for 2014-2023 (BGUS) in reference to the debate on functional and normative regions. The synthetic and normative treatment of development corridors in BGUS seems problematic in terms of the conceptualization of functional regions in a dynamic and realistic manner. The structural problems of development planning in Turkey since the 1950s signify the need for redefining development corridors as functional regions addressing the concerns of governance, functional linkages, core and hinterland interactions and the modifiable areal unit problem. What is suggested in this paper is that a holistic and multi-layer approach is more suitable for delineating the development corridors in Turkey rather than a threefold classification in BGUS (development, transportation and tourism corridors)
Biblioteka Regionalisty, 2019, Nr 19, s. 161-167
Keywords: Dolny Śląsk